Smallanthus sonchifolius (Yacon) leaves: an emerging source of compounds for diabetes management - Honore, Stella Maris (2015)
Diabetes mellitus is a chronic metabolic disease that develops mainly due to insulin deficiency or resistance to insulin action. All forms of diabetes are characterized by chronic hyperglycemia, which has an important role in the pathogenesis of diabetic complications. Leaves of Smallanthus sonchifolius (Poepp.&Endl.) H. Robinson (yacon) have been used since ancient times to prepare medicinal herbal tea with beneficial health properties. This review aims to discuss some key aspects related to the potential use of S. sonchifolius leaves and their natural biomolecules for the prophylaxis and treatment of diabetes as well as the potential mechanisms of action.